Oxidation resistance and emissivity of diboride-based composites containing tantalum disilicide in air plasma up to 2600 K for space applications. Issue 19 (1st October 2022) - Pellegrini, C.; Balat-Pichelin, M.; Rapaud, O.; Bêche, E.
Abstract: Fully-dense ZrB2 and HfB2 composites were elaborated by Spark Plasma Sintering with 20 vol% TaSi2 to replace SiC in the aim of improving their oxidation resistance. This study follows the one carried out on (Zr/Hf)B2 –SiC systems in the same oxidation conditions. The oxidation behavior of ZrB2 –20%TaSi2 and HfB2 -20%TaSi2 in air plasma conditions, at 1000 Pa total pressure and from 1950 K up to 2600 K, was studied using the MESOX facility implemented at the focus of the 6 kW Odeillo solar furnace. The mass variation of the samples during an oxidation duration of 300 s on a temperature plateau was followed. A four step oxidation mechanism is proposed. A good oxidation behavior, with a slight mass gain, has been identified up to 2170 K due to the formation of a refractory mixed oxide (Hf/Zr)6 Ta2 O17 at the surface of the samples. An improvement of the oxidation resistance by 200 K is obtained compared to the composites with SiC as additional compound. Moreover, as emissivity is an important parameter for space applications and that oxidation plays a huge role on the evolution of the emissivity, the normal spectral emissivity was measured on several pre-oxidized samples using atomic oxygen (representative surfaces) and the normal total emissivity was calculated. Finally, for both the compositions, the emissivity is comprised between 0.80 and 0.90 in the temperature range 1300–2200 K.